Estimation of the moduli of continuity of one-variable functions in the metric of L in terms of fourier coefficients - Telyakovskii, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
This paper is a survey of results concerning the estimation of the moduli of continuity of functions in the metric of L in terms of their Fourier coefficients. Upper bounds, lower bounds, and asymptotic estimates of the moduli of continuity are presented.